Internal Tandem Duplication of Exon 8 of c-kit Is Associated With Longer Total Survival in Canine Cutaneous Mast Cell Tumors. Issue 2 (March 2021) - Brocks, Bouvien A. W.; Bertram, Christof A.; Bartel, Alexander; Kirpensteijn, Jolle; Collins-Webb, Alexandra; Catlin, Chuck; Thaiwong, Tuddow; Kiupel, Matti
Canine cutaneous mast cell tumors (ccMCTs) have a highly variable biological behavior and accurate prognostication is essential for therapeutic intervention. Internal tandem duplications (ITD) of exon 11 are the most commonly detected c-kit mutation in ccMCTs and are associated with poor prognosis and increased cellular proliferation. The prognostic value of detecting mutations in other exons of c-kit has not been systematically examined. In this study, we analyzed the prognostic value of ITD mutations of exon 8 in c-kit of ccMCTs in comparison to ccMCTs with ITD mutations of exon 11 and ccMCTs without mutations of exon 8 or 11. The mutational status, histological grade, KIT expression pattern, Ki67 index, AgNOR (argyrophilic nucleolar organizing region) score, and Ag67 score were determined in 221 ccMCTs, and outcome was available for 101 dogs. ITD mutations of exon 8 were found in 73/221 (33%), of exon 11 in 100/221 (45%), and none of these mutations in 50/221 (22%) of ccMCTs. None of the dogs with mutations of exon 8 died due to suspected ccMCT-related cause, but 23% dogs with ccMCTs with mutations of exon 11 died due to suspected ccMCT-related cause. Prognostic parameters in ccMCTs with exon 11 mutations were commonly associated with a high proliferative activity and poor prognosis, while prognostic markers in ccMCTs with mutations of exon 8 had lower values similar to those observed in ccMCTs without mutations in exons 8 or 11 of c-kit . This study indicates that screening for ITD mutations in exon 8 in ccMCTs may be helpful to identify less aggressive ccMCTs and may be recommended as a supplementary prognostic test.